2014
DOI: 10.1016/j.rser.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

An international review of the implications of regulatory and electricity market structures on the emergence of grid scale electricity storage

Abstract: Wade NS. An international review of the implications of regulatory and electricity market structures on the emergence of grid scale electricity storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 58 publications
(98 reference statements)
0
59
0
5
Order By: Relevance
“…Institutional adaptation-oriented research has contributed with knowledge on the adaptation of the existing regulatory framework [85][86][87][88][89][90], with analysis of different regulatory approaches, such as incentive regulation [91][92][93], and innovative methods to stimulate electricity distribution adaptation to smart grids [94][95][96], which often include regulatory recommendations for NRAs [97], [98]. In addition to a number of studies on the impact of regulatory frameworks on adaptation [99][100][101][102][103], the branches of research presented are but a sample of the ongoing progress aiming at a better understanding of the technological and institutional changes necessary to the transition towards smarter and more sustainable electricity distribution.…”
Section: Electricity Distribution Adaptation To a Smarter And More Sumentioning
confidence: 99%
“…Institutional adaptation-oriented research has contributed with knowledge on the adaptation of the existing regulatory framework [85][86][87][88][89][90], with analysis of different regulatory approaches, such as incentive regulation [91][92][93], and innovative methods to stimulate electricity distribution adaptation to smart grids [94][95][96], which often include regulatory recommendations for NRAs [97], [98]. In addition to a number of studies on the impact of regulatory frameworks on adaptation [99][100][101][102][103], the branches of research presented are but a sample of the ongoing progress aiming at a better understanding of the technological and institutional changes necessary to the transition towards smarter and more sustainable electricity distribution.…”
Section: Electricity Distribution Adaptation To a Smarter And More Sumentioning
confidence: 99%
“…This paper builds on the paper by Anuta et al (2014) [24] that provides an extensive review of the regulatory and policy environments relating to energy storage in several countries with high renewable energy targets. Our work complements this by providing an historical context to the development of PHES and an overview of current market environments for PHES in the electricity markets of several countries (UK, USA, Germany, Japan, China, Switzerland and India).…”
Section: Novel Bulk Ees Technologies Under Development Include Adiabamentioning
confidence: 99%
“…As a result Japan has pioneered a seawater pumped hydro scheme on Okinawa Island [32]. Historically Japan has also had some of the highest electricity prices in OECD countries [24]. It should be noted that Japan is actively pursuing other EES storage options and has developed as a leader in sodium sulphur (NaS) grid-scale electrochemical battery installations [33].…”
Section: Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy storage has already been investigated and shown that it has the potential to increase the robustness and reliability of energy systems, to reduce the price volatility in electricity market with govern the price structure and to deliver renewable generation to loads [4], [5]. Technologybased systems modelling which can combine the necessary temporal granularity to accurately represents ES is essential [6].…”
Section: Introductionmentioning
confidence: 99%